UNIT 1E.3 Genome‐Wide Fitness and Genetic Interactions Determined by Tn‐seq, a High‐Throughput Massively Parallel Sequencing Method for Microorganisms. Issue 1 (2nd February 2015) - van Opijnen, Tim; Lazinski, David W.; Camilli, Andrew
Abstract : The lagging annotation of bacterial genomes and the inherent genetic complexity of many phenotypes is hindering the discovery of new drug targets and the development of new antimicrobial agents and vaccines. This unit presents Tn‐seq, a method that has made it possible to quantitatively determine fitness for most genes in a microorganism and to screen for quantitative genetic interactions on a genome‐wide scale and in a high‐throughput fashion. Tn‐seq can thus direct studies on the annotation of genes and untangle complex phenotypes. The method is based on the construction of a saturated transposon insertion library. After library selection, changes in the frequency of each insertion mutant are determined by sequencing flanking regions en masse. These changes are used to calculate each mutant's fitness. The method was originally developed for the Gram‐positive bacterium Streptococcus pneumoniae, a causative agent of pneumonia and meningitis, but has now been applied to several different microbial species. © 2015 by John Wiley & Sons, Inc.